Altered Mitochondrial Dynamics Contributes to Endothelial Dysfunction in Diabetes Mellitus - Shenouda, Sherene M.; Widlansky, Michael E.; Chen, Kai; Xu, Guoquan; Holbrook, Monika; Tabit, Corey E.; Hamburg, Naomi M.; Frame, Alissa A.; Caiano, Tara L.; Kluge, Matthew A.; Duess, Mai-Ann; Levit, Aaron; et al. (Circulation (New York, N.Y.), 2011)
Endothelial dysfunction contributes to the development of atherosclerosis in patients with diabetes mellitus, but the mechanisms of endothelial dysfunction in this setting are incompletely understood. Recent studies have shown altered mitochondrial dynamics in diabetes mellitus with increased mitochondrial fission and production of reactive oxygen species. We investigated the contribution of altered dynamics to endothelial dysfunction in diabetes mellitus. We observed mitochondrial fragmentation (P=0.002) and increased expression of fission-1 protein (Fis1; P<0.0001) in venous endothelial cells freshly isolated from patients with diabetes mellitus (n=10) compared with healthy control subjects (n=9). In cultured human aortic endothelial cells exposed to 30 mmol/L glucose, we observed a similar loss of mitochondrial networks and increased expression of Fis1 and dynamin-related protein-1 (Drp1), proteins required for mitochondrial fission. Altered mitochondrial dynamics was associated with increased mitochondrial reactive oxygen species production and a marked impairment of agonist-stimulated activation of endothelial nitric oxide synthase and cGMP production. Silencing Fis1 or Drp1 expression with siRNA blunted high glucose-induced alterations in mitochondrial networks, reactive oxygen species production, endothelial nitric oxide synthase activation, and cGMP production. An intracellular reactive oxygen species scavenger provided no additional benefit, suggesting that increased mitochondrial fission may impair endothelial function via increased reactive oxygen species. These findings implicate increased mitochondrial fission as a contributing mechanism for endothelial dysfunction in diabetic states.